Respons Histopatologik Karsinoma Serviks Uteri Setelah Pemberian Kemoradiasi - T Mirza Iskandar; Maria Mexitalia; Sarjadi Sarjadi; Edi Dharmana; Noor Pramono (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTFactors associated with histopathologic responses of cervical cancer after chemoradiation therapyIntroduction: Cervical carcinoma is the second most common women cancer in the world. A combined of surgical, radiation and chemotherapy is the main cervical carcinoma treatment. The histopathological response is one performance to assess the result of the treatment. The purpose of the study is to analyze the factors of cervical cancer which contributes to the histopathological response after chemoradiation treatment.Methods: The design of the study was a case control, done at Dr. Kariadi Hospital Semarang in 2008. Patients with biopsy-proven cervical carcinoma were entered into the study. The variables of risk factors included the stage of the cancer by FIGO staging, the type and differentiation of the tumour, the anemia and the history of the transfusion and the immunotherapy by BCG vaccine. The histopathological response was assessed after the chemoradiation treatment. Chi-square was used to analyze the risk factors and logistic regression was used for the multivariate analysis.Results: Between April-August 2008, 77 patients finished the chemoradiation treatment. The type of the cancer was squamous cell carcinoma (71.4%) and the stage was III B (81.8%). The staging, type and differentiation of the tumor, and the history of transfusion did not contributes to the histopathological response. After adjustment of other factors, the contribution of anemia to poor histopathological response were 6.25 times (95% CI 1.12-34.90; p=0.037) higher than good histopahological response.Conclusion: Anemia is the risk factor of poor histopathological response of cervical carcinoma after chemoradiation therapy.Keywords: Cervical carcinoma, chemoradiation, histopahological responseABSTRAKPendahuluan: Karsinoma serviks uteri (KSU) merupakan kanker kedua terbanyak pada wanita di seluruh dunia. Sampai saat ini terapi pilihan utama KSU adalah operasi, radiasi dan kemoterapi. Salah satu penilaian keberhasilan terapi adalah dengan respon histopatologik. Tujuan penelitian ini adalah menilai faktor-faktor yang berperan terhadap respons histopatologik setelah terapi kemoradiasi.Metode: Desain penelitian adalah kasus kontrol. Penelitian dilakukan di RSUP Dr. Kariadi Semarang. Kriteria inklusi adalah KSU yang telah menyelesaikan kemoradiasi. Faktor-faktor yang dinilai berperan terhadap respons histopatologi adalah tipe histologis dan diferensiasi tumor, stadium tumor berdasarkan FIGO, anemia dan riwayat transfusi serta pemberian imunoterapi dengan BCG. Analisis statistik menggunakan kai-kuadrat dan regresi logistik.Hasil: Selama periode April-Agustus 2008 terdapat 77 penderita yang menyelesaikan kemoradiasi. Sebagian besar penderita berada pada stadium IIIB (71,4%) dan mempunyai tipe histologi karsinoma sel skuamosa (81,8%). Stadium tumor, tipe histologi dan diferensiasi tumor, riwayat transfusi serta imunoterapi BCG tidak berperan pada respons histopatologik. Setelah memperhitungkan faktor perancu, risiko anemia terhadap respons histopatologi yang jelek adalah 6,25 kali (95% CI 1,12-34,90; p=0,037).Simpulan: Anemia merupakan faktor risiko terjadinya respon histopatologik yang jelek pada penderita karsinoma serviks uterisetelah mendapatkan terapi kemoradiasi.